2015
DOI: 10.1589/jpts.27.1075
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mental practice on stroke patients’ upper extremity function and daily activity performance

Abstract: [Purpose] The purpose of this study was to evaluate the effects of mental practice on stroke patients’ upper extremity function and activities of daily living (ADL). [Subjects and Methods] In this study, 29 stroke patients were randomly assigned to two groups: an experimental group (n=14) and a control group (n=15). The experimental group performed 10 minutes of mental practice once a day, 5 days a week for 2 weeks in combination with conventional rehabilitation therapy. For the control group, general rehabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(46 citation statements)
references
References 14 publications
1
42
0
3
Order By: Relevance
“…However, when there is a significant reduction in overall physical functioning in addition to motor function, it has been found that such repetitive practice can be a cause of both fatigue and reduced motivation for rehabilitation 1 ) . Meanwhile, research in sports training has shown that combining mental practice with physical practice enhances the effects of training relative to physical practice alone 2 , 3 , 4 , 5 ) .…”
Section: Introductionmentioning
confidence: 99%
“…However, when there is a significant reduction in overall physical functioning in addition to motor function, it has been found that such repetitive practice can be a cause of both fatigue and reduced motivation for rehabilitation 1 ) . Meanwhile, research in sports training has shown that combining mental practice with physical practice enhances the effects of training relative to physical practice alone 2 , 3 , 4 , 5 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Of those articles, 2 were excluded because they were not completed studies Therefore, a total of nine articles were reviewed and classified according to the criteria described earlier. The results are summarized in Table 1 [1][2][3][4][5]. …”
Section: Resultsmentioning
confidence: 99%
“…The upper limb part of the FMA includes the reflex activity; extensor flexor synergy movement; cooperative motion activities; cooperative movement activities; no hyperreflexia; wrist, elbow and straight shoulder flexion stability of 90 degrees; finger movement and coordination ability; and speed. The Modified Barthel Index (MBI) evaluates the activity of daily living [27]. It consists of a total of 10 items; full marks indicate a score of 100, including excretion, grooming, using the toilet, eating, transformation (bed to chair), walking activities (walking in or around the ward, not including a long walk), dressing, bathing, walking up and down the stairs.…”
Section: Motor Function and Ability Of Daily Life Assessmentmentioning
confidence: 99%